The citizen-candidate model with imperfect policy control - R. Emre Aytimur; Aristotelis Boukouras; Robert Schwager (Center for Economic Studies and ifo Institute (CESifo), 2012)
We examine the two-candidate equilibria of the citizen-candidate model when the implemented policy arises from a compromise between the government and an unelected external power. We show that the equilibria of this model differ significantly from the original: the distance between the candidates' policies, both ideal and implemented, remains strictly above a threshold. Thus, the median voters' ideal policy may not obtain in contested elections if policy control is imperfect, even when the cost of running as a candidate is arbitrarily small.
Keywords: D72; D78; H11; 330; elections; polarization; strategic delegation; bureaucracy; foreign influence; Wahl; Median Voter; Bürokratie; Kooperative Führung; Theorie